Resin composition, and molded body

Through the combination of specific thermoplastic polymers and carbon materials, the problem of insignificant functions in composite materials is solved, and performance improvements such as higher mechanical strength, electrical conductivity and thermal conductivity are achieved, forming a stronger synergistic effect.

JP2025019432APending Publication Date: 2025-02-07NIX INC +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123043
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the molded bodies of thermoplastic polymer and carbon material composites are difficult to fully exert their respective functions, and the functional enhancement effect is not significant, especially the performance improvement in mechanical strength, electrical conductivity and thermal conductivity is limited.

Method used

Using a combination of specific thermoplastic polymers and carbon materials, by controlling their specific peak intensity ratio and half-width in the Raman spectrum, the carbon material is uniformly dispersed in the thermoplastic polymer, forming better chemical and electrical affinity, thereby enhancing the functional performance of the composite material.

Benefits of technology

The full play of the functions of thermoplastic polymers and carbon materials has been achieved, and the mechanical strength, electrical conductivity, thermal conductivity and electromagnetic wave shielding of the molded body have been significantly improved, forming a stronger synergistic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019432000041
    Figure 2025019432000041
  • Figure 2025019432000042
    Figure 2025019432000042
  • Figure 2025019432000043
    Figure 2025019432000043
Patent Text Reader

Abstract

To provide a resin composition from which a molded body sufficiently having a function derived from a thermoplastic polymer and a function derived from a carbon material can be suitably obtained, and a molded body.SOLUTION: A resin composition contains a thermoplastic polymer (A) and a carbon material (B), wherein the thermoplastic polymer (A) contains a monomer unit having a dipolar moment of 4.1 debye or more, the carbon material (B) shows peaks in the vicinity of 1,360 cm-1 and the vicinity of 1,580 cm-1, in a Raman spectrum obtained using a laser Raman spectroscopy, when integrated intensity of a peak observed in the vicinity of 1,360 cm-1 is represented by ID and integrated intensity of a peak observed in the vicinity of 1,580 cm-1 is represented by IG, an intensity ratio ID / IG (R value) is 1.80 or less, and a half-value width of the peak observed in the vicinity of 1,580 cm-1 is 55 cm-1 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article. [Background technology]

[0002] Thermoplastic polymers are used in a wide variety of fields, such as automobiles, aircraft, power generation equipment, and sports and leisure goods, because of their moldability and ease of recycling. In addition, by using a filler together with the thermoplastic polymer, the obtained molded article can be endowed with the functions of the thermoplastic polymer and the filler.

[0003] Carbon materials are widely used as such fillers. By blending a carbon material with a thermoplastic polymer and compositing these components, it is expected that the molded product will be endowed with various functions that the carbon material possesses, such as mechanical strength, sliding properties, electrical conductivity, thermal conductivity, electromagnetic wave shielding properties, vibration damping properties, X-ray transparency, and low thermal expansion properties (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-171887 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in reality, it is not possible to sufficiently impart the functions derived from the thermoplastic polymer and the functions derived from the carbon material to the molded body, and there is a problem that it is difficult to obtain a synergistic effect derived from these functions. For example, in a molded body obtained by blending a carbon material with a thermoplastic polymer, the elastic modulus is usually about 1 / 10 to 1 / 100 of the elastic modulus of the carbon material alone. In addition, the conductivity of the molded body can usually only be expressed to about 1 / 1,000,000 of the conductivity of the carbon material alone.

[0006] The present invention has been made in consideration of such problems, and an object of the present invention is to provide a resin composition that can be used to preferably obtain a molded article that has more sufficiently both the functions derived from a thermoplastic polymer and the functions derived from a carbon material, and a molded article. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have found that by using a resin composition containing a specific thermoplastic polymer and a specific carbon material, the obtained molded article more fully possesses the functions derived from the thermoplastic polymer and the functions derived from the carbon material, and exerts a greater synergistic effect derived from these functions, thereby completing the present invention.

[0008] The present invention includes the following embodiments. [1] A resin composition comprising a thermoplastic polymer (A) and a carbon material (B), wherein the thermoplastic polymer (A) contains a monomer unit having a dipole moment of 4.1 debye or more, and the carbon material (B) has a dipole moment of 1360 cm in a Raman spectrum obtained by laser Raman spectroscopy. -1 Near and 1580cm -1 Each peak is around 1360cm -1 The integrated intensity of the peak observed near I D and 1580cm -1 The integrated intensity of the peak observed near I G The intensity ratio I D / I G (R value) is 1.80 or less, and 1580 cm -1 The half-width of the peak observed around 55 cm -1 A resin composition comprising:

[0009] [2] The resin composition according to [1], wherein the thermoplastic polymer (A) comprises at least one selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), polyetherimide (PEI), polyamide 66 (PA66), polyethylene terephthalate (PET), liquid crystal polymer (LCP3), liquid crystal polymer (LCP1), polyetheretherketone (PEEK), polyamide 6 (PA6), polyamideimide (PAI), and polyarylate (PAR).

[0010] [3] The resin composition according to [1] or [2], wherein the carbon material (B) comprises at least one selected from the group consisting of carbon fibers, carbon nanotubes, graphite, and graphene.

[0011] [4] The resin composition according to any one of [1] to [3], wherein the aspect ratio of the carbon material (B) is 1.0 or more and 30,000,000 or less.

[0012] [5] The resin composition according to any one of [1] to [4], wherein a mass ratio of the thermoplastic polymer (A) to the carbon material (B) (the thermoplastic polymer (A):the carbon material (B)) is 10.0:90.0 or more and 99.9:0.1 or less.

[0013] [6] The resin composition according to any one of [1] to [5], further comprising a thermoplastic resin (C) different from the thermoplastic polymer (A).

[0014] [7] The resin composition according to [6], wherein the content of the thermoplastic resin (C) is 1.0 part by mass or more and 90.0 parts by mass or less per 100 parts by mass of the total resin solid content in the resin composition.

[0015] [8] The resin composition according to any one of [1] to [7], further comprising an inorganic filler (D) different from the carbon material (B).

[0016] [9] The resin composition according to [8], wherein the content of the inorganic filler (D) is 0.1 parts by mass or more and 900.0 parts by mass or less per 100 parts by mass of the total resin solid content in the resin composition.

[0017]

[10] A molded article comprising the resin composition according to any one of [1] to [9]. Effect of the Invention

[0018] According to the present invention, it is possible to provide a resin composition that can be used to obtain a molded article having a function derived from a thermoplastic polymer and a function derived from a carbon material more sufficiently. Furthermore, by using the resin composition, it is possible to more sufficiently impart the function derived from a thermoplastic polymer and the function derived from a carbon material, and it is possible to obtain a molded article that exhibits a synergistic effect derived from these functions. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 shows Raman spectra of carbon materials (B5 and D1). [Diagram 2] FIG. 2 is a diagram showing a Raman spectrum obtained by processing the Raman spectrum of the carbon material (B5) shown in FIG. 1 using a Lorentz function. [Diagram 3] FIG. 2 is a diagram showing a Raman spectrum obtained by processing the Raman spectrum of the carbon material (D1) shown in FIG. 1 using a Lorentz function. [Figure 4] FIG. 1 is a diagram showing the intensity ratio ID / IG (R value) and the half-width of the peak in a carbon material (B) and an inorganic filler (D). [Diagram 5] FIG. 2 is a schematic diagram showing a front view and a left side view of a U-shaped bearing molded for a sliding test. [Figure 6] FIG. 1 is a diagram showing the relationship between the dipole moment in a thermoplastic polymer (A) and a thermoplastic resin (C), a carbon material (B) and an inorganic filler (D), and the strength increase rate. [Figure 7]FIG. 1 is a diagram showing the relationship between the dipole moment in a thermoplastic polymer (A) and a thermoplastic resin (C), a carbon material (B) and an inorganic filler (D), and the amount of wear of a U-shaped bearing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described with reference to the drawings as necessary. The present embodiment is an example for explaining the present invention, and the present invention is not limited to the embodiment.

[0021] In this embodiment, unless otherwise specified, the "resin solid content" or the "resin solid content in the resin composition" refers to the components in the resin composition excluding the carbon material (B), the inorganic filler (D), the additives, and the organic solvent, and "100 parts by mass of the resin solid content in the resin composition" refers to 100 parts by mass of the total of the components in the resin composition excluding the carbon material (B), the inorganic filler (D), the additives, and the organic solvent.

[0022] [Resin composition] The resin composition of the present embodiment contains a thermoplastic polymer (A) (hereinafter also simply referred to as a “thermoplastic polymer”) and a carbon material (B) (hereinafter also simply referred to as a “carbon material”). The thermoplastic polymer (A) contains a monomer unit having a dipole moment of 4.1 debye or more. The carbon material (B) has a dipole moment of 1360 cm or more in a Raman spectrum obtained by laser Raman spectroscopy. -1 Near and 1580cm -1 Each peak is around 1360cm -1 The integrated intensity of the peak observed near I D and 1580cm -1 The integrated intensity of the peak observed near I G The intensity ratio I D / I G (R value) is 1.80 or less, and 1580 cm -1 The half-width of the peak observed around 55 cm -1 The following is the result.

[0023] According to the resin composition of the present embodiment, it is possible to more fully impart the functions derived from the thermoplastic polymer and the functions derived from the carbon material, and it is possible to suitably obtain a molded article that exhibits a synergistic effect derived from these functions. Although the reason for this is unclear, the present inventors presume it to be as follows.

[0024] The carbon material has poor affinity and adhesion with the thermoplastic polymer, and is aggregated in the thermoplastic polymer, making it difficult to disperse uniformly. Therefore, the reinforcing effect of the carbon material does not extend to the entire thermoplastic polymer, and conductive paths and heat conductive paths are not sufficiently formed. For this reason, it is presumed that the molded body has difficulty in exerting various functions. In order to increase the affinity and adhesion between the carbon material and the thermoplastic polymer, it is possible to perform a surface treatment on the carbon material or to modify the thermoplastic polymer, but there are problems in that the range of application of the carbon material and the thermoplastic polymer is limited, and the process is complicated.

[0025] Based on this assumption, we investigated the prior literature and found that prior literature 1 (Maliang Zhang, Xiaotion Wang, Chenyang Li, Yali Bai, Bowen Cheng and Zhenhuan Li, RSC Adv., 2016, 6. 92378-92386) describes how the polarity of PPS (polyphenylene sulfide) resin, a thermoplastic polymer, and carboxylic acid-modified carbon nanotubes (COOH-CNT) electronically attract each other, improving the strength of the resulting molded body.

[0026] In addition, prior literature 2 (Yunjie Lin, Junjin Che, Shuiqin Pu, Ke Wang, POLYMER COMPOSITES, E589-E598, 2019) and prior literature 3 (Yao Gao, Qiang Fu, Liyuan Niu, Zimu Shi, Jornal of Material Science, 50:3622-360, 2015) have shown that when a sample made by thermally melting a thermoplastic polymer, PPS resin, and carbon nanotubes (CNTs) and processing them into a dumbbell shape is stretched at a low speed in an atmosphere higher than the crystallization temperature, the aromatic structure of the thermoplastic polymer and the graphite structure of the CNTs are electronically attracted to each other, improving the strength of the resulting molded body.

[0027] From these prior documents, we have made extensive investigations focusing on the polarity of thermoplastic polymers and the structure of carbon materials. As a result, we have focused on the dipole moment as an indicator of the polarity of thermoplastic polymers, and on the dipole moment at 1360 cm in Raman spectra obtained by laser Raman spectroscopy as an indicator of the structure of carbon materials. -1 The peak observed around 1580 cm (hereinafter referred to as the "D band") and -1 The authors focused on a peak observed near the dipole moment of 4.1 debye or more in the D band and the G band (hereinafter, also referred to as the "G band"). D / I G , R value) is 1.80 or less, and the half-width of the G band is 55 cm -1 It has been found that by using the carbon material described below, a highly polar monomer unit in a thermoplastic polymer and a carbon material having a developed graphite crystal structure due to high crystallinity are electronically attracted to each other more favorably with a strong Coulomb force, and excellent chemical affinity is obtained.

[0028] As a result, the carbon material has good affinity and adhesion with the thermoplastic polymer, and the carbon material does not aggregate in the thermoplastic polymer and can be uniformly dispersed. Therefore, the reinforcing effect of the carbon material spreads to the entire thermoplastic polymer, and conductive paths and heat conductive paths are sufficiently formed. And, according to such a resin composition, the electronic and chemical affinity between the carbon material and the thermoplastic polymer is further improved in the molded body, so that the functions derived from both the thermoplastic polymer and the carbon material can be sufficiently imparted to the molded body without impairing the functions derived from the thermoplastic polymer and the functions derived from the carbon material. From this, it is presumed that a molded body having a synergistic effect can be obtained. However, the reason for the presumption is not limited to this.

[0029] According to the resin composition of the present embodiment, by blending a thermoplastic polymer having excellent processability as the thermoplastic polymer and a carbon material with the thermoplastic polymer, it is possible to obtain a molded article having improved processability and reduced weight by replacing metal, for example.

[0030] According to the resin composition of the present embodiment, a reinforcing effect derived from the carbon material can be obtained in the entire thermoplastic polymer, so that a molded article having improved mechanical strength and vibration damping properties can be obtained.

[0031] Since the thermoplastic polymer and the carbon material are uniformly dispersed, the carbon material can be present on the surface of the molded article without being unevenly distributed, and therefore a molded article having superior sliding properties can be obtained.

[0032] By uniformly dispersing the thermoplastic polymer and the carbon material, the conductive paths and the thermal conductive paths are more fully formed, and therefore it is possible to obtain a molded article having superior electrical conductivity, thermal conductivity, and thermal expansion coefficient.

[0033] Since the thermoplastic polymer and the carbon material are uniformly dispersed, the entire molded article exhibits electromagnetic wave shielding properties, making it possible to obtain a molded article having superior electromagnetic wave shielding properties.

[0034] [Thermoplastic polymer (A)] The resin composition of the present embodiment contains a thermoplastic polymer (A). The thermoplastic polymer (A) contains a monomer unit having a dipole moment of 4.1 debye or more.

[0035] The thermoplastic polymer has thermoplasticity and contains one or more monomer units having a dipole moment of 4.1 debye or more. The thermoplastic polymer is a polymer or a copolymer. The copolymer may be a random copolymer or a block copolymer. The thermoplastic polymer may be used alone or in combination of two or more.

[0036] The mass average molecular weight of the thermoplastic polymer is usually from 1,000 to 15,000,000, and preferably from 1,000 to 500,000. In this specification, the mass average molecular weight is a value calculated in terms of standard polystyrene by GPC (gel permeation chromatography).

[0037] In this specification, when the thermoplastic polymer is a homopolymer, the homopolymer is composed of a monomer unit having a dipole moment of 4.1 debye or more. For example, in the case of a binary copolymer having a repeat number a of a monomer unit A and a repeat number b of a monomer unit B as shown in the following formula (I), the monomer unit having a dipole moment of 4.1 debye or more in the binary copolymer may be the monomer unit A or the monomer unit B, or may be both the monomer unit A and the monomer unit B. The dipole moments of the monomer unit A and the monomer unit B may be the same or different. In the case of a multicomponent copolymer, the multicomponent copolymer may have at least one monomer unit having a dipole moment of 4.1 debye or more.

[0038] [ka]

[0039] In the thermoplastic polymer, the dipole moment can be calculated, for example, by ab initio quantum chemical calculation. A specific method for calculating the dipole moment is as described in the Examples.

[0040] The dipole moment of the monomer unit is preferably 4.3 debye or more, more preferably 4.5 debye or more, even more preferably 5.0 debye or more, and even more preferably 6.0 debye or more. By using a thermoplastic polymer containing a monomer unit having a dipole moment in the above range, it is possible to obtain a resin composition having better affinity and adhesion with carbon materials. The upper limit of the dipole moment is, for example, 12.0 debye or less.

[0041] Examples of thermoplastic polymers containing a monomer unit having a dipole moment of 4.1 debye or more include thermoplastic polymers represented by formulas (1) to (13). By using such a thermoplastic polymer, it tends to be possible to obtain a resin composition having better affinity and adhesion to carbon materials.

[0042] [ka]

[0043] In the polysulfone (PSU) represented by formula (1), the dipole moment of the monomer unit is 9.8 debye. 1 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 1 is preferably a hydrogen atom. 1 is usually between 1 and 40,000. 1 is preferably 3 or more and 3000 or less.

[0044] [ka]

[0045] In the polyphenylsulfone (PPSU) represented by formula (2), the dipole moment of the monomer unit is 7.8 debye. 2 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 2 is preferably a hydrogen atom. 2 is usually between 1 and 40,000. 2 is preferably 3 or more and 3000 or less.

[0046] [ka]

[0047] In polyamide 10T (PA10T) represented by formula (3), the dipole moment of the monomer unit is 7.3 debye. 3 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 3 is preferably a hydrogen atom. 3 is usually between 1 and 40,000. 3 is preferably 3 or more and 3000 or less.

[0048] [ka]

[0049] In the polyethersulfone (PES) represented by formula (4), the dipole moment of the monomer unit is 7.0 debye. 4 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 4 is preferably a hydrogen atom. 4 is usually between 1 and 40,000. 4 is preferably 3 or more and 3000 or less.

[0050] [ka]

[0051] In the polyetherimide (PEI) represented by formula (5), the dipole moment of the monomer unit is 6.9 debye. 5 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 5 is preferably a hydrogen atom. 5 is usually between 1 and 40,000. 5 is preferably 3 or more and 3000 or less.

[0052] [ka]

[0053] In polyamide 66 (PA66) represented by formula (6), the dipole moment of the monomer unit is 6.6 debye. 6 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 6 is preferably a hydrogen atom. 6 is usually between 1 and 40,000. 6 is preferably 3 or more and 3000 or less.

[0054] [ka]

[0055] In polyethylene terephthalate (PET) represented by formula (7), the dipole moment of the monomer unit is 6.5 debye. 7 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 7is preferably a hydrogen atom. 7 is usually between 1 and 40,000. 7 is preferably 3 or more and 3000 or less.

[0056] [ka]

[0057] The thermoplastic polymer represented by formula (8) has a repeating unit x 1 Monomer units of and repeating units y 1 The repeating unit x 1 The monomer unit of is 3.4 debye, and the repeat unit y 1 The monomer unit is 6.5 debye. Examples of the thermoplastic polymer represented by formula (8) include liquid crystal polymer (LCP3A) and liquid crystal polymer (LCP3B).

[0058] In the liquid crystal polymer (LCP3A), R in formula (8) 8 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 8 is preferably a hydrogen atom. 1 is 70 mol% or more and 90 mol% or less, and y 1 is 10 mol% or more and 30 mol% or less, provided that x 1 +y 1 is 100 mol%.

[0059] In the liquid crystal polymer (LCP3B), R in formula (8) 8 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 8 is preferably a hydrogen atom. 1 is 50 mol% or more and 70 mol% or less, and y 1 is 30 mol% or more and 50 mol% or less, provided that x 1 +y 1 is 100 mol%.

[0060] [ka]

[0061] The thermoplastic polymer represented by formula (9) has a repeating unit x 2 Monomer unit, repeat unit y 2 Monomer units of and repeating units z 2 The repeating unit x 2 The monomer unit of is 3.4 debye, and the repeat unit y 2 The monomer unit of is 1.2 debye, and the repeat unit z 2 The monomer unit of is 4.5 debye. An example of the thermoplastic polymer represented by formula (9) is liquid crystal polymer (LCP1). In liquid crystal polymer (LCP1), R 9 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 9 is preferably a hydrogen atom. 2 is 50 mol% or more and 70 mol% or less, and y 2 is 15 mol% or more and 25 mol% or less, z 2 is 15 mol% or more and 25 mol% or less, provided that x 2 +y 2 +z 2 is 100 mol%.

[0062] [ka]

[0063] In polyether ether ketone (PEEK) represented by formula (10), the dipole moment of the monomer unit is 4.6 debye. 10 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 10 is preferably a hydrogen atom. 8 is usually between 1 and 40,000. 8is preferably 3 or more and 3000 or less.

[0064] [ka]

[0065] In polyamide 6 (PA6) represented by formula (11), the dipole moment of the monomer unit is 4.1 debye. 11 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 11 is preferably a hydrogen atom. 9 is usually between 1 and 40,000. 9 is preferably 3 or more and 3000 or less.

[0066] [ka]

[0067] In the polyamideimide (PAI) represented by formula (12), the dipole moment of the monomer unit is 4.3 debye. 12 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 12 is preferably a hydrogen atom. 10 is usually between 1 and 40,000. 10 is preferably 3 or more and 3000 or less.

[0068] [ka]

[0069] In the polyarylate (PAR) represented by formula (13), the dipole moment of the monomer unit is 6.5 debye. 13R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 13 is preferably a hydrogen atom. 11 is usually between 1 and 40,000. 11 is preferably 3 or more and 3000 or less.

[0070] The thermoplastic polymer preferably includes at least one selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), polyetherimide (PEI), polyamide 66 (PA66), polyethylene terephthalate (PET), liquid crystal polymer (LCP3), liquid crystal polymer (LCP1), polyetheretherketone (PEEK), polyamide 6 (PA6), polyamideimide (PAI), and polyarylate (PAR). The thermoplastic polymer preferably includes at least one selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), polyetherimide (PEI), polyamide 66 (PA66), polyethylene terephthalate (PET), liquid crystal polymer (LCP3), liquid crystal polymer (LCP1), polyetheretherketone (PEEK), and polyamide 6 (PA6). The thermoplastic polymer preferably includes at least one selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), and polyetherimide (PEI). By using such a thermoplastic polymer, it is possible to obtain a resin composition having better affinity and adhesion to carbon materials.

[0071] The mass ratio of the thermoplastic polymer (A) to the carbon material (B) (thermoplastic polymer (A):carbon material (B)) is preferably 10.0:90.0 or more and 99.9:0.1 or less, more preferably 15.0:85.0 or more and 95.0:5.0 or less, even more preferably 20.0:80.0 or more and 90.0:10.0 or less, and even more preferably 30.0:70.0 or more and 85.0:15.0 or less. By having the mass ratio of the thermoplastic polymer to the carbon material in the above range, it tends to be possible to obtain a resin composition in which the affinity and adhesion between the thermoplastic polymer and the carbon material are better.

[0072] The content of the thermoplastic polymer (A) is preferably 10.0 parts by mass or more and 100.0 parts by mass or less, and may be 10.0 parts by mass or more and 99.0 parts by mass or less, 15.0 parts by mass or more and 95.0 parts by mass or less, 20.0 parts by mass or more and 90.0 parts by mass or less, 25.0 parts by mass or more and 85.0 parts by mass or less, or 30.0 parts by mass or more and 80.0 parts by mass or less, based on 100 parts by mass of the resin solid content in the resin composition. By having the content of the thermoplastic polymer in the above range, it is possible to obtain a resin composition having better affinity and adhesion to the carbon material.

[0073] The thermoplastic polymer can be produced by any known method as long as the desired thermoplastic polymer can be obtained by the method, for example, a method of polymerizing a monomer constituting a monomer unit using a known radical polymerization initiator or radical chain transfer agent.

[0074] [Carbon material (B)] The resin composition of the present embodiment contains a carbon material (B). The carbon material (B) has a peak at 1360 cm in a Raman spectrum obtained by laser Raman spectroscopy. -1 Near and 1580cm -1 Each peak is around 1360cm -1 The integrated intensity of the peak observed near I D and 1580cm -1 The integrated intensity of the peak observed near IG The intensity ratio I D / I G (R value) is 1.80 or less, and 1580 cm -1 The half-width of the peak observed around 55 cm -1 The carbon materials can be used alone or in combination of two or more.

[0075] The Raman spectrum can be obtained, for example, by using a laser Raman spectrophotometer under the following conditions.

[0076] (conditions) Analytical equipment: Laser Raman spectrophotometer, Nd:YVO 4 Laser wavelength: 532 nm, slit: φ17 μm, central wavelength: 2300 cm -1 , Exposure time: 1 second, Number of accumulations: 3.

[0077] In this specification, the Raman spectrum obtained by this Raman spectroscopy is processed using a fitting function, and the peak at 1340 cm -1 Over 1390cm -1 The peak that appears around 1360 cm -1 The peak observed near the 1550 cm -1 More than 1600cm -1 The peaks that appear around 1580 cm -1 The fitting function can be, for example, the Lorentz function or the Voigt function. -1 The integrated intensity of the peak due to the disorder and defects in the graphite structure observed near I (hereinafter also referred to as the "D band intensity") is D He is 1580cm tall. -1 The integrated intensity of the peak due to the perfect graphite structure, which is derived from the in-plane motion of carbon atoms observed near the G This is called the intensity ratio I D / I GThe R value is calculated as the ratio of the D band intensity to the G band intensity. -1 The half-width of the peak observed around 1520 cm is the full-width at half maximum (FWHM) of the G band. -1 Over 1540cm -1 Near or below 1620cm -1 Peaks are observed around 1000 nm. These peaks are due to defects in the crystal structure and are different from the D band and G band, so they are called other peaks. The fitting process of the Raman spectrum can be performed using a normal data processing program. Examples of such data processing programs include Igor Pro (trade name, Hulinks Co., Ltd.), Excel (registered trademark, Microsoft), and the data expression program Origin Pro (trade name, Lightstone Co., Ltd.).

[0078] In addition, the intensity ratio I D / I G An example of a method for calculating the (R value) and half width will be described with reference to Figures 1 to 3. By measuring a carbon material using a laser Raman spectrophotometer, for example, a Raman spectrum as shown in Figure 1 can be obtained.

[0079] FIG. 1 shows a Raman spectrum of a carbon material (B5, corresponding to the carbon material B5 described in the Examples) and a Raman spectrum of a carbon material (D1, corresponding to the inorganic filler D1 described in the Examples). FIG. 2 shows a Raman spectrum of the carbon material (B5) shown in FIG. 1, which is processed using a Lorentz function. FIG. 3 shows a Raman spectrum of the carbon material (D1) shown in FIG. 1, which is processed using a Lorentz function. In FIGS. 1 to 3, the horizontal axis represents the Raman shift (Raman Shift, cm -1 ), and the vertical axis represents Raman scattering intensity (intensity, arbitrary unit: arb.).

[0080] As shown in the Raman spectra of Figures 2 and 3, when the Raman spectrum obtained by Raman spectroscopy is subjected to fitting processing using the Lorentz function (data processing program), the D band, G band, and other peaks are obtained. In addition, the data processing program calculates the D band intensity and the G band intensity based on these D band and G band, and further calculates the intensity ratio I D / I G (R value) is calculated, and the half-width is calculated from the G band. Note that fitting is done using the corrected R 2 This is done so that the value is 0.995 or higher.

[0081] When the fitting process was performed as described above, the carbon material (B5) had an R value of 0.33 and a half-width of 25 cm -1 The inorganic filler (D1) had an R value of 4.30 and a half-value width of 85 cm -1 It was calculated that:

[0082] The R value is preferably 1.70 or less, more preferably 1.50 or less, even more preferably 1.00 or less, and even more preferably 0.50 or less. By using a carbon material having an R value in the above range, it is possible to obtain a resin composition having better affinity and adhesion with a thermoplastic polymer. The upper limit is, for example, 0.01 or more due to the detection limit in Raman spectroscopy.

[0083] The half-width is preferably 50 cm -1 Less than or equal to 44 cm, more preferably -1 Less than or equal to 42 cm, and more preferably -1 and even more preferably 39 cm or less. -1 By using a carbon material having a half-width in the above range, it is possible to obtain a resin composition having better affinity and adhesion with a thermoplastic polymer. The lower limit is, for example, 1 cm due to the detection limit in Raman spectroscopy. -1 That's all.

[0084] The aspect ratio of the carbon material is preferably 1.0 to 30,000,000, more preferably 5.0 to 26,000,000, even more preferably 10.0 to 10,000,000, even more preferably 15.0 to 5,000,000, and even more preferably 20.0 to 1,000,000. By using a carbon material having an aspect ratio in the above range, it is possible to obtain a resin composition having better affinity and adhesion with a thermoplastic polymer. In this specification, the aspect ratio means the value of the fiber length (mm) of the carbon material relative to the fiber diameter (μm) of the carbon material, that is, the value of the fiber length of the carbon material / the fiber diameter of the carbon material×1000. The aspect ratio may be, for example, obtained by randomly collecting 100 carbon materials and calculating the average value from the aspect ratios of these carbon materials. The aspect ratio may be a value calculated using the nominal values ​​(catalog values) of the fiber length and fiber diameter of the carbon material. For specific methods of measuring and calculating the aspect ratio, see the Examples.

[0085] Examples of carbon materials include carbon fibers, carbon nanotubes (CNTs), whiskers, graphite (GR), graphene, fullerene (C60), and carbon black (CB).

[0086] The carbon material preferably includes at least one selected from the group consisting of carbon fiber, carbon nanotube, graphite, and graphene. The carbon material preferably includes at least one selected from the group consisting of carbon fiber and carbon nanotube. By using these carbon materials, it is likely that a resin composition having better affinity and adhesion with the thermoplastic polymer can be obtained.

[0087] Examples of the carbon fiber include milled fiber, chopped fiber, and long fiber. For the reason of processability into a molded product, the carbon fiber preferably includes at least one type selected from the group consisting of milled fiber and chopped fiber.

[0088] Carbon nanotubes include, for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT).

[0089] Examples of whiskers include fullerene whiskers, graphene whiskers, and graphite whiskers.

[0090] Examples of graphite include natural graphite, artificial graphite, and highly oriented pyrolytic graphite.

[0091] Examples of graphene include graphene oxide, nanographene, and graphene nanoribbons.

[0092] As fullerenes, for example, C 60 , C 70 , C 80 and mixtures thereof.

[0093] Examples of carbon black include furnace black, channel black, acetylene black, and thermal black.

[0094] The content of the carbon material (B) is preferably 0.1 parts by mass or more and 900.0 parts by mass or less, more preferably 2.0 parts by mass or more and 570.0 parts by mass or less, even more preferably 3.0 parts by mass or more and 430.0 parts by mass or less, still more preferably 5.0 parts by mass or more and 400.0 parts by mass or less, and particularly preferably 10.0 parts by mass or more and 300.0 parts by mass or less, relative to 100 parts by mass of the resin solid content in the resin composition. By having the content of the carbon material in the above range, it tends to be possible to obtain a resin composition having better affinity and adhesion to the thermoplastic polymer.

[0095] The carbon material can be produced by any known method without any particular limitation as long as the desired carbon material can be obtained by the production method.

[0096] [Thermoplastic resin (C)] The resin composition of the present embodiment may further contain a thermoplastic resin (C) (hereinafter, also simply referred to as "thermoplastic resin") different from the thermoplastic polymer (A). When the thermoplastic resin contains one or more types of monomer units, the dipole moments of the monomer units are all less than 4.1 debye. The thermoplastic resin may be a polymer or a copolymer. The copolymer may be a random copolymer or a block copolymer. The thermoplastic resin may be a thermoplastic resin that does not contain one or more types of monomer units. The thermoplastic resin may be used alone or in combination of two or more types.

[0097] Examples of thermoplastic resins containing a monomer unit having a dipole moment of less than 4.1 debye include thermoplastic resins represented by formulas (14) to (21). By using such thermoplastic resins, it tends to be possible to impart physical properties to a molded article that cannot be obtained by using the thermoplastic polymer (A) alone.

[0098] [ka]

[0099] The thermoplastic resin represented by formula (14) has a repeating unit x 3 Monomer units of and repeating units y 3 The repeat unit x 3 The dipole moment of the monomer unit is 3.4 debye, and the repeat unit y 3 The dipole moment of the monomer unit is 3.1 debye. An example of the thermoplastic resin represented by formula (14) is liquid crystal polymer (LCP2). In liquid crystal polymer (LCP2), R 14 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 14 is preferably a hydrogen atom. 3is 65 mol% or more and 85 mol% or less, and y 3 is 15 mol% or more and 35 mol% or less, provided that x 3 +y 3 is 100 mol%.

[0100] [ka]

[0101] In the polyoxymethylene (POM) represented by formula (15), the dipole moment of the monomer unit is 2.3 debye. 15 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 15 is preferably a hydrogen atom. 12 is usually between 1 and 40,000. 12 is preferably 3 or more and 3000 or less.

[0102] [ka]

[0103] In polyphenylene sulfide (PPS) represented by formula (16), the dipole moment of the monomer unit is 1.9 debye. 16 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 16 is preferably a hydrogen atom. 13 is usually between 1 and 40,000. 13 is preferably 3 or more and 3000 or less.

[0104] [ka]

[0105] In the polycarbonate (PC) represented by formula (17), the dipole moment of the monomer unit is 1.9 debye. 17 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 17 is preferably a hydrogen atom. 14 is usually between 1 and 40,000. 14 is preferably 3 or more and 3000 or less.

[0106] [ka]

[0107] In the polyphenylene ether (PPE) represented by formula (18), the dipole moment of the monomer unit is 1.7 debye. 18 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 18 is preferably a hydrogen atom. 15 is usually between 1 and 40,000. 15 is preferably 3 or more and 3000 or less.

[0108] [ka]

[0109] In polystyrene (PS) represented by formula (19), the dipole moment of the monomer unit is 0.2 debye. 19 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 19 is preferably a hydrogen atom. 16 is usually between 1 and 40,000. 16 is preferably 3 or more and 3000 or less.

[0110] [ka]

[0111] In polypropylene (PP) represented by formula (20), the dipole moment of the monomer unit is 0.1 debye. 20 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 20 is preferably a hydrogen atom. 17 is usually between 1 and 40,000. 17 is preferably 3 or more and 3000 or less.

[0112] [ka]

[0113] In the polyethylene (PE) represented by formula (21), the dipole moment of the monomer unit is 0.0 debye. 21 R each independently represents a hydrogen atom, a methyl group, or an ethyl group. 21 is preferably a hydrogen atom. 18 is usually between 1 and 40,000. 18 is preferably 3 or more and 3000 or less.

[0114] The thermoplastic resin preferably contains at least one selected from the group consisting of a liquid crystal polymer (LCP2) different from the thermoplastic polymer (A), polyoxymethylene (POM), polyphenylene sulfide (PPS), polycarbonate (PC), polyphenylene ether (PPE), polystyrene (PS), polypropylene (PP), polyethylene (PE), and modified products thereof. The thermoplastic resin more preferably contains at least one selected from the group consisting of a liquid crystal polymer (LCP2) different from the thermoplastic polymer (A), polyoxymethylene (POM), polyphenylene sulfide (PPS), polycarbonate (PC), polyphenylene ether (PPE), polystyrene (PS), and polypropylene (PP). Even in such a thermoplastic resin (C), by using the thermoplastic polymer (A) in combination, there is a tendency that a resin composition having good affinity and adhesion with the carbon material (B) can be obtained. Even when the resin composition further contains an inorganic filler (D) described below, it tends to be possible to obtain a resin composition in which the affinity and adhesion of each component is good.

[0115] The mass ratio of the thermoplastic polymer (A) to the thermoplastic resin (C) (thermoplastic polymer (A): thermoplastic resin (C)) may be 10.0:90.0 or more and 99.0:1.0 or less, 15.0:85.0 or more and 95.0:5.0 or less, 20.0:80.0 or more and 90.0:10.0 or less, or 30.0:70.0 or more and 85.0:15.0 or less. By having the mass ratio of the thermoplastic polymer to the thermoplastic resin in the above range, it is possible to obtain a resin composition in which the affinity and adhesion between the thermoplastic polymer (A), the thermoplastic resin (C), and the carbon material (B) are better. In addition, even when the resin composition further contains an inorganic filler (D) described later, it is possible to obtain a resin composition in which the affinity and adhesion between each component are good.

[0116] The content of the thermoplastic resin (C) may be 1.0 parts by mass or more and 90.0 parts by mass or less, 5.0 parts by mass or more and 85.0 parts by mass or less, 10.0 parts by mass or more and 80.0 parts by mass or less, 15.0 parts by mass or more and 75.0 parts by mass or less, or 20.0 parts by mass or more and 70.0 parts by mass or less, based on 100 parts by mass of the resin solid content in the resin composition. By having the content of the thermoplastic resin in the above range, it is likely that a resin composition having better affinity and adhesion between the thermoplastic polymer (A), the thermoplastic resin (C), and the carbon material (B) can be obtained. In addition, even when the resin composition further contains an inorganic filler (D) described later, it is likely that a resin composition having good affinity and adhesion between each component can be obtained.

[0117] [Inorganic filler (D)] The resin composition of the present embodiment may further contain an inorganic filler (D) (hereinafter, also simply referred to as "inorganic filler") different from the carbon material (B). The inorganic filler may be used alone or in combination of two or more kinds.

[0118] Examples of inorganic fillers include carbon materials other than the carbon material (B) (hereinafter also simply referred to as "carbon material (D)"), zinc oxide, potassium titanate, aramid fibers, glass fibers, asbestos fibers, silica fibers, alumina fibers, silica-alumina fibers, aluminum silicate fibers, zirconia fibers, potassium titanate fibers, silicon carbide fibers, boron fibers, whiskers (silicon carbide whiskers, alumina whiskers, silicon nitride whiskers, potassium titanate whiskers, barium titanate whiskers, wollastonite whiskers, aluminum borate whiskers), glass beads, aluminum silicate, glass beads, talc, mica, glass flakes, glass powder, milled glass fibers, wollastonite, and metal fibers (iron, gold, copper, aluminum, brass, and stainless steel).

[0119] The carbon material (D) is a material having a peak at 1360 cm in a Raman spectrum obtained by processing a Raman spectrum obtained by using a fitting function based on the Raman spectrum obtained by using laser Raman spectroscopy. -1 Near and 1580cm -1 The carbon material (D) is a carbon material that does not exhibit a peak at either or both of the regions near 1360 cm in a Raman spectrum obtained by processing a Raman spectrum obtained by using laser Raman spectroscopy with a fitting function. -1 Near and 1580cm -1 Each peak is around 1360cm -1 The integrated intensity of the peak observed near I D and 1580cm -1 The integrated intensity of the peak observed near I G The intensity ratio I D / I G (R value) exceeds 1.80 and is 1580 cm -1 The half-width of the peak observed near the -1 (iii) a carbon material having a temperature of 1,360 cm or less; -1 Near and 1580cm -1 The peaks are in the vicinity of each other, and the intensity ratio I D / I G (R value) is 1.80 or less, and 1580 cm -1 The half-width of the peak observed near the -1 and (iv) carbon materials having a wavelength greater than 1360 cm -1 Near and 1580cm -1 The peaks are in the vicinity of each other, and the intensity ratio I D / I G (R value) exceeds 1.80 and is 1580 cm -1 The half-width of the peak observed near the -1 The carbon material (D) may be used alone or in combination of two or more.

[0120] The mass ratio of the carbon material (B) to the inorganic filler (D) (carbon material (B): inorganic filler (D)) may be 99.0:1.0 or more and 10.0:90.0 or less, 95.0:5.0 or more and 20.0:80.0 or less, 90.0:10.0 or more and 30.0:70.0 or less, or 85.0:15.0 or more and 50.0:50.0 or less. By having the mass ratio of the carbon material (B) to the inorganic filler (D) in the above range, it is possible to obtain a resin composition in which the affinity and adhesion between the thermoplastic polymer (A), the carbon material (B), and the inorganic filler (D) are better. In addition, even when the resin composition further contains a thermoplastic resin (C) or the like, it is possible to obtain a resin composition in which the affinity and adhesion between each component are good.

[0121] The content of the inorganic filler (D) may be 0.1 parts by mass or more and 900.0 parts by mass or less, 0.5 parts by mass or more and 450.0 parts by mass or less, 1.0 parts by mass or more and 100.0 parts by mass or less, 3.0 parts by mass or more and 75.0 parts by mass or less, or 5.0 parts by mass or more and 50.0 parts by mass or less, relative to 100 parts by mass of the resin solid content in the resin composition. By having the content of the inorganic filler in the above range, it is likely to be possible to obtain a resin composition in which the affinity and adhesion between the thermoplastic polymer (A), the carbon material (B), and the inorganic filler (D) are better. In addition, even when the resin composition further contains a thermoplastic resin (C) or the like, it is likely to be possible to obtain a resin composition in which the affinity and adhesion between each component is good.

[0122] [Additives] The resin composition of the present embodiment may further contain an additive. The additive is different from the thermoplastic polymer (A), the carbon material (B), the thermoplastic resin (C), and the inorganic filler (D). The additive may be used alone or in combination of two or more.

[0123] Examples of the additives include antioxidants, ultraviolet absorbers, dyes, pigments, thickeners, lubricants, defoamers, leveling agents, gloss agents, flame retardants, ion trapping agents, light stabilizers, plasticizers, nucleating agents, and antistatic agents.

[0124] Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], bis-[3,3-bis-(4'-hydroxy-3'-tert-butylphenyl)butanoic acid]-glycol ester, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, and thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. hindered phenolic antioxidants such as octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(methylene-2,4,6-triyl)tri-p-cresol, hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, and methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; Examples of phosphorus-based antioxidants include tris(2,4-di-tert-butylphenyl)phosphite, tris[2-[[2,4,8,10-tetra-tert-butylbenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol phosphite, bis(2,6-di-tert-butyl-4-phenyl)pentaerythritol phosphite, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.

[0125] The antioxidant may be a commercially available product, such as CY1770 (product name) manufactured by Solvay Japan K.K.

[0126] Examples of ultraviolet absorbers include 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol, propanediol, and [(4-methoxyphenyl)-methylene]-dimethyl ester.

[0127] The ultraviolet absorbing agent may be a commercially available product, such as Tinuvin 1600 (product name) manufactured by BAFS Japan Co., Ltd.

[0128] The content of each additive is usually 0.01 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the resin solid content in the resin composition.

[0129] [Organic solvent] The resin composition of the present embodiment may further contain an organic solvent. The organic solvent may be used alone or in combination of two or more kinds.

[0130] Examples of the organic solvent include amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; esters such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, α-methyl-γ-butyrolactone, ethyl lactate, methyl acetate, ethyl acetate, and butyl acetate; aliphatic alcohols having 1 to 10 carbon atoms such as methanol, ethanol, and propanol; aromatic group-containing phenols such as phenol and cresol; benzyl alcohol, etc. aromatic group-containing alcohols such as those mentioned above; glycols such as ethylene glycol and propylene glycol, or monoethers or diethers of these glycols with methanol, ethanol, butanol, hexanol, octanol, benzyl alcohol, phenol, cresol, or the like, or esters of these monoethers; cyclic ethers such as dioxane and tetrahydrofuran; carbonates such as ethylene carbonate and propylene carbonate; aliphatic and aromatic hydrocarbons such as benzene, naphthalene, toluene, and xylene; and aprotic polar solvents such as dimethyl sulfoxide.

[0131] [Method for producing resin composition] The method for producing the resin composition of the present embodiment is not particularly limited as long as it can produce a resin composition having the above-mentioned composition. The resin composition can be prepared, for example, by appropriately mixing a thermoplastic polymer (A), a carbon material (B), and, if necessary, a thermoplastic resin (C), an inorganic filler (D), and an additive. If necessary, these components may be dissolved or dispersed in an organic solvent to produce a varnish. For specific production methods, see the examples.

[0132] [Molded body] The molded article of the present embodiment contains a resin composition.

[0133] The molded article according to the present embodiment can reduce energy consumption more effectively than metal materials. In addition, when compared with the same resin material, thermoplastic polymers are more suitable for recycling than thermosetting resins, making it possible to achieve decarbonization. As a result, it can contribute to the realization of a sustainable society.

[0134] The molded article can be used in a variety of applications. Examples of such applications include transportation equipment, automobile parts (e.g., motor control valves, engine cooling modules, fuel system housings, and frames), electric vehicle parts (e.g., motor insulators; PCU cases such as inverters, DC / DC converters, current sensors, and reactors; impellers and bearings for cooling pumps), sports bikes, pedals, housings (e.g., infrastructure, robots, and drones), motor bearings (e.g., water heaters, vacuum cleaners, and ventilation fans), and the automotive and aerospace industries (e.g., side beams, doors, and other components). panels, hinges, suspension arms, propeller shafts, frames, bumpers, front ends, hoods, bodies, tire rims, combustion equipment covers, cowls, and heat measurement components); sporting goods (e.g., tennis racquets, golf clubs, bats, and skis); the medical industry (e.g., medical devices such as surgical tools and x-ray equipment; artificial joints, bones, arms, and legs); and the electrical and electronics industry (e.g., electronic equipment exteriors, mounts, protective covers, heat sinks, housings, and trays).

[0135] The molded article can be obtained by using the resin composition and applying an appropriate known molding method such as, for example, injection molding, compression molding, transfer molding, extrusion molding, blow molding, calendar molding, FRP molding, laminate molding, cast molding, solution casting, vacuum / pressure molding, extrusion composite molding, foam molding, thermoforming, insert molding, melt impregnation, and melt spinning. The shape of the molded product is not particularly limited, and may be any shape such as a flat plate, a rod, a cylinder, a comb, a sphere, etc. The resin composition may be molded by itself, or may be combined with a metal or the like to perform two-color or multi-color molding. EXAMPLES

[0136] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to these examples. Furthermore, "parts" and "%" are by mass unless otherwise specified.

[0137] [Raw material evaluation] (1) Dipole moment The dipole moment (Debye) of the thermoplastic polymer (A) and the thermoplastic resin (C) used in the examples and comparative examples was calculated by the following method.

[0138] First, for each monomer unit constituting the thermoplastic polymer and thermoplastic resin, the molecular structure was drawn using MolView to obtain data for each monomer unit. Then, using the quantum computing software Firefly (Alex A. Granovsky, Firefly version 8, www http: / / classic.chem.msu.su / gran / firefly / index.html, J. Comput.Chem. 14, 1347-1363 (1993)), the data was analyzed under the following conditions, and the dipole moment (debye) for each monomer unit was calculated. Among the dipole moments of each monomer unit obtained, the dipole moment of the monomer unit with the highest dipole moment was taken as the dipole moment of the thermoplastic polymer and thermoplastic resin. The calculation of the dipole moment is based on the above, but a known method may also be used. Firefly is an application that performs ab initio quantum chemical calculations and is quantum computing software that can calculate the electronic states of molecules using various quantum chemical theories, such as Hartree-Fock theory, density functional theory, many-body perturbation theory, and coordination interaction theory.

[0139] (conditions) JOB type;Geometry Optimization, Wavefunction;RHF, MP-Pertubation;0, Method;6-31G*, DFT-Type;NONE, Solvant;NONE, Charge;0, Spin Stage;Single

[0140] (2) Intensity ratio I D / I G (R value) and half-width of peak Intensity ratio I in the carbon material (B) and inorganic filler (D) used in the examples and comparative examples D / I G The (R value) and half width of the peak were measured by the following method.

[0141] That is, the carbon material or the inorganic filler was measured under the following conditions using laser Raman spectroscopy to obtain the Raman spectrum of the carbon material or the inorganic filler. The Raman spectrum obtained was fitted with the Lorentz function using the data expression program Origin Pro (trade name, manufactured by Lightstone Corporation) to obtain the peak at 1360 cm -1 The integrated intensity (I D ) and 1580cm -1 The integrated intensity (I G ) and the intensity ratio I D / I G (R value) was calculated. In addition, the 1580 cm -1 The half-width was calculated using the peak observed around 1520 cm. In addition to the above, in all carbon materials (B) and inorganic fillers (D) other than inorganic filler (D16), the half-width was calculated using the peak observed around 1520 cm. -1 Over 1540cm -1 Near or below 1620cm -1 Peaks were observed around 1360 cm. These peaks were due to defects in the crystal structure. In addition, the inorganic filler (D16) had a peak around 1360 cm. -1 Near and 1580cm -1 No peaks were observed nearby.

[0142] (conditions) Analytical equipment: Laser Raman spectrophotometer NRS-4500 (product name, manufactured by JASCO Corporation), Nd:YVO 4 Laser wavelength: 532 nm, slit: φ17 μm, central wavelength: 2300 cm -1 , Exposure time: 1 second, Number of accumulations: 3.

[0143] (3) Aspect ratio The aspect ratios of the carbon material (B) and the inorganic filler (D) used in the examples and comparative examples were calculated from the following formula (II) using the nominal values ​​(catalog values) of the average fiber length (mm) and the fiber diameter (μm). Aspect ratio = average fiber length / average fiber diameter × 1000 … (II)

[0144] [Dipole moments of thermoplastic polymers and thermoplastic resins] The dipole moments of the thermoplastic polymers (A) and thermoplastic resins (C) used in the examples and comparative examples were calculated based on the above-mentioned evaluation method. The results are shown in Table 1.

[0145] The thermoplastic polymers and thermoplastic resins shown in Table 1 are as follows: In Table 1, for the copolymers, the dipole moment of each monomer unit is shown.

[0146] (Thermoplastic polymer (A)) (A1) PSU: polysulfone represented by formula (1) (Udel (registered trademark) P-1700 (trade name) manufactured by Solvay Japan Co., Ltd., homopolymer, R 1 is a hydrogen atom) (A2) PPSU...polyphenylsulfone represented by formula (2) (Radel (registered trademark) R-5000 (product name), manufactured by Solvay Japan Co., Ltd., homopolymer, R 2 is a hydrogen atom) (A3) PA10T: Polyamide 10T represented by formula (3) (XecoT (registered trademark) XN400 (product name), manufactured by Unitika Ltd., homopolymer, R 3 is a hydrogen atom) (A4) PES: polyethersulfone represented by formula (4) (Sumikaexcel (registered trademark) 3600G (product name) manufactured by Sumitomo Chemical Co., Ltd., homopolymer, R 4 is a hydrogen atom) (A5) PEI...polyetherimide represented by formula (5) (Ultem (registered trademark) 1000 (product name) manufactured by SABIC, homopolymer, R 5 is a hydrogen atom) (A6) PA66...Polyamide 66 represented by formula (6) (Unika Nylon 66, E2000 (trade name), homopolymer, manufactured by Unitika Ltd.) 6 is a hydrogen atom) (A7) PET...polyethylene terephthalate represented by formula (7) (Kuraray Co., Ltd., Kurapet (registered trademark) KS710B-8S (product name) homopolymer, R 7 is a hydrogen atom) (A8-1) LCP3A: Thermoplastic polymer represented by formula (8) (wherein x 1 is 80 (mol%), and y 1 Liquid crystal polymer having a monomer unit with a molar ratio of 20 (mol%), LCP3A, Rodrum (registered trademark) LC-5000 (product name) manufactured by Unitika Ltd., liquid crystal transition temperature: 285°C, random copolymer, R 8 is a hydrogen atom) (A8-2) LCP3B: Thermoplastic polymer represented by formula (8) (wherein x 1 is 60 (mol%), and y 1 Liquid crystal polymer having a monomer unit with a molar ratio of 40 (mol%), LCP3B, Rodrum (registered trademark) LC-3000 (product name) manufactured by Unitika Ltd., liquid crystal transition temperature: 185°C, random copolymer, R 8 is a hydrogen atom) (A9) LCP1: Thermoplastic polymer represented by formula (9) (wherein, x 2 is 60 (mol%), and y 2 is 20 (mol%), z 2 A liquid crystal polymer having a monomer unit in which the amount of a monomer unit is 20 (mol%), LCP1, Cider (registered trademark) STR500 (product name) manufactured by ENEOS Liquid Crystal Co., Ltd., a random copolymer, R9 is a hydrogen atom) (A10) PEEK: polyether ether ketone represented by formula (10) (VICTREX (registered trademark) 90G (product name) manufactured by Victrex, homopolymer, R 10 is a hydrogen atom) (A11) PA6...Polyamide 6 represented by formula (11) (Amilan (registered trademark) CM1017 (product name) manufactured by Toray Industries, Inc., homopolymer, R 11 is a hydrogen atom)

[0147] (Thermoplastic resin (C)) (C1) LCP2: Thermoplastic resin represented by formula (14) (wherein x 3 is 73 (mol%), and y 3 Liquid crystal polymer having a monomer unit with a molar ratio of 27 (mol%), LCP2, Vectra (registered trademark) A950 (trade name) manufactured by Celanese Japan Co., Ltd., liquid crystal transition temperature: 280° C., random copolymer, R 14 is a hydrogen atom) (C2) POM...polyoxymethylene represented by formula (15) (TENAC (registered trademark) 4010 (product name) manufactured by Asahi Kasei Corporation, homopolymer, R 15 is a hydrogen atom) (C3) PPS...polyphenylene sulfide represented by formula (16) (FZ-2100 (trade name) manufactured by DIC Corporation, homopolymer, R 16 is a hydrogen atom) (C4) PC...polycarbonate represented by formula (17) (Iupiace (registered trademark) S-3000 (product name), manufactured by Global Polyacetal Co., Ltd., homopolymer, R 17 is a hydrogen atom) (C5) PPE...polyphenylene ether represented by formula (18) (manufactured by Mitsubishi Gas Chemical Company, Inc., Iupiace (registered trademark) AH91 (product name), homopolymer, R 18 is a hydrogen atom) (C6) PS...polystyrene represented by formula (19) (DIC Styrene (registered trademark) CR-3500 (trade name) manufactured by DIC Corporation, homopolymer, R 19 is a hydrogen atom) (C7) PP...polypropylene represented by formula (20) (Novatec (registered trademark) MA3 (product name), injection molding grade, homopolymer, manufactured by Japan Polypropylene Corporation) 20 is a hydrogen atom)

[0148] [Table 1]

[0149] [Intensity ratio I for carbon material (B) and inorganic filler (D) D / I G (R value, and half-width of peak) Intensity ratio I in the carbon material (B) and inorganic filler (D) used in the examples and comparative examples D / I G The R value and the half-width of the peak were measured by the above-mentioned method. The aspect ratios of the carbon material (B) and the inorganic filler (D) were calculated by the above-mentioned method. The results are shown in Table 2 and FIG. 4 together with the shapes of the carbon material (B) and the inorganic filler (D).

[0150] The carbon material (B) and inorganic filler (D) shown in Table 2 are as follows.

[0151] (Carbon material (B)) (B1) tuball...single-walled carbon nanotubes (CNT, OCSiAl tuball (product name), average fiber length: 0.005 mm, fiber diameter: 0.0016 μm) (B2) MWCNT: Multi-walled carbon nanotubes (CNT, manufactured by Koatsu Gas Kogyo Co., Ltd., average fiber length: 1000 mm, fiber diameter: 0.04 μm) (B3) K223HE...chopped fiber (carbon fiber, Mitsubishi Chemical Corporation's DIALEAD (registered trademark) K223HE (product name), average fiber length: 6 mm, fiber diameter: 11 μm) (B4) K223HM... Milled fiber (carbon fiber, Mitsubishi Chemical Corporation's DIALEAD (registered trademark) K223HM (product name), average fiber length: 0.2 mm, fiber diameter: 11 μm) (B5) XN100... Milled fiber (carbon fiber, GRANOC (registered trademark) XN-100 (product name) manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length: 0.25 mm, fiber diameter: 10 μm) (B6) ZY300... Milled fiber (carbon fiber, GRANOC (registered trademark) ZY300 (product name) manufactured by Mitsubishi Chemical Corporation, average fiber length: 0.25 mm, fiber diameter: 11 μm) (B7) K6371T... chopped fiber (carbon fiber, Mitsubishi Chemical Corporation DIALEAD (registered trademark) K6371T (product name), average fiber length: 6 mm, fiber diameter: 11 μm) (B8) XN-80... Milled fiber (carbon fiber, GRANOC (registered trademark) XN-80 (product name) manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length: 0.25 mm, fiber diameter: 10 μm) (B9) XN-60... Milled fiber (carbon fiber, GRANOC (registered trademark) XN-60 (product name) manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length: 0.25 mm, fiber diameter: 10 μm) (B10) Graphene oxide...graphene (Log9 Materials Scientific Private Limited, GO (trade name), average fiber length: 1 mm, fiber diameter: 20 μm) (B11) GE-1...Graphite (natural graphite, Ito Graphite Industries Co., Ltd. GE-1, average fiber length: 0.002 mm, fiber diameter: 2 μm, volume resistivity: 8 mΩ cm) (B12) namuno mix...fullerene (namuno mix manufactured by Frontier Carbon Co., Ltd., average fiber length: 0.03 mm, fiber diameter: 30 μm)

[0152] (Inorganic filler (D)) (D1) HT... chopped fiber (carbon fiber, Teijin Ltd. HT-C702 (product name), average fiber length: 6 mm, fiber diameter: 7 μm) (D2) IM... chopped fiber (carbon fiber, Teijin Ltd. IM-C702 (product name), average fiber length: 6 mm, fiber diameter: 5 m) (D3) K223SE... Milled fiber (carbon fiber, Mitsubishi Chemical Corporation's DIALEAD (registered trademark) K223SE (product name), average fiber length: 0.2 mm, fiber diameter: 11 μm) (D4) T700... Milled fiber (carbon fiber, Toray Industries, Inc., Torayca (registered trademark) T-700 (product name), average fiber length: 0.2 mm, fiber diameter: 7 μm) (D5) XN-10... Milled fiber (carbon fiber, GRANOC (registered trademark) XN-10 (product name) manufactured by Nippon Graphite Fiber Co., Ltd., average fiber length: 0.25 mm, fiber diameter: 10 μm) (D6) MR03NE...chopped fiber (carbon fiber, PYROFIL (registered trademark) MR03NE (product name) manufactured by Mitsubishi Chemical Corporation, average fiber length: 6 mm, fiber diameter: 7 μm) (D7) TR03ML...chopped fiber (carbon fiber, PYROFIL (registered trademark) TR03ML (product name) manufactured by Mitsubishi Chemical Corporation, average fiber length: 6 mm, fiber diameter: 7 μm) (D8) T300... Milled fiber (carbon fiber, Toray Industries, Inc., Torayca (registered trademark) T300 (product name), average fiber length: 0.2 mm, fiber diameter: 7 μm) (D9) TNMC0...multi-walled carbon nanotubes (carbon nanotubes surface-modified with carboxyl and hydroxyl groups, TNMC0 (product name) manufactured by Timesnano, average fiber length: 0.02 mm, fiber diameter: 0.006 μm) (D10) #3030B...Carbon black (Mitsubishi Chemical Corporation Mitsubishi Carbon Black #3030B, average fiber length: 0.055 mm, fiber diameter: 55 μm, volume resistivity: 140 mΩ cm) (D16) CS3PE-256...Glass fiber (Nitto Boseki Co., Ltd. Cut Fiber CS3PE-256, fiber length: 3 mm, fiber diameter: 13 μm)

[0153] [Table 2]

[0154] Example 1 (Preparation of resin composition) A resin composition was obtained by kneading 80% by mass of the thermoplastic polymer (A1) and 20% by mass of the carbon material (B3) at a processing temperature of 360°C and a rotation speed of 75 rpm for 5 minutes using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.). The composition (% by mass) and processing temperature (°C) are shown in Table 3.

[0155] The obtained resin composition was injection molded using a simple injection molding machine (IMC-18D1 (product name) manufactured by Imoto Manufacturing Co., Ltd.) under conditions of a cylinder temperature of 380°C and a mold temperature of 200°C, to obtain dumbbell test pieces (1 / 2 dumbbell test pieces) that were half the size of dumbbell-shaped tensile test pieces type A conforming to JIS K7139 (2009). Furthermore, the obtained resin composition was injection molded using a simple injection molding machine (IMC-18D1 (product name) manufactured by Imoto Machinery Works) under the same conditions as those for molding the 1 / 2 dumbbell test pieces, i.e., a cylinder temperature of 380°C and a mold temperature of 200°C, to obtain a U-shaped bearing. As shown in FIG. 5, in the front view of the U-shaped bearing, the radius (r) of the part that would become the inner receiving part of the U-shape was 4 mm, the radius (R) of the outer part was 7 mm, the thickness (T) was 3 mm, and the width (W) was 14 mm. In addition, in the left side view of the U-shaped bearing, the depth (D) was 8 mm, and the height (H) was 7 mm. Table 3 shows the cylinder temperature and mold temperature during molding of the 1 / 2 dumbbell test pieces and U-shaped bearings.

[0156] (Evaluation of Resin Composition) (1) Tensile strength test The 1 / 2 dumbbell test piece obtained in Example 1 was stretched at a speed of 5 mm / min using a precision universal testing machine (Autograph AG-X (product name) manufactured by Shimadzu Corporation), and the tensile breaking strength (unit: MPa) was measured when the test piece broke. The results are shown in Table 3.

[0157] (2) Sliding test First, the mass A (g) of the U-shaped bearing obtained in Example 1 was measured using an analytical balance (AP125WD-AD (product name) manufactured by Shimadzu Corporation). After that, using a journal sliding tester (manufactured in-house), a SUS304 shaft (diameter: 6 mm) was slid against the receiving part of the U-shaped bearing for 200 hours under conditions of a load of 1 kg and a rotation speed of 4,000 rpm, and then the mass B (g) of the U-shaped bearing was measured. The amount of wear (mg) was calculated as the difference between mass A and B (mass A - mass B). The results are shown in Table 3.

[0158] [Examples 2 to 13, and 18 to 25] (Preparation of resin composition) Resin compositions in Examples 2 to 13 and 18 to 25 were prepared in the same manner as in Example 1, except that the thermoplastic polymer (A) and the carbon material (B) were changed so as to have the composition shown in Table 3. In Examples 2 to 13 and 18 to 25, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperature shown in Table 3. The rotation speed and kneading time were the same as in Example 1. The components shown in Table 3 are as described above.

[0159] Example 14 (Preparation of resin composition) 90 parts by mass of the thermoplastic polymer (A5) was added to 500 mL of N-methyl-2-pyrrolidone as an organic solvent, and the mixture was heated for 1 hour to obtain a resin solution.

[0160] In addition, 10 parts by mass of the carbon material (B1) was added to 500 mL of N-methyl-2-pyrrolidone as an organic solvent, and ultrasonically treated with stirring for 1 hour using a laboratory ultrasonic homogenizer (UP400S (product name) manufactured by Dr. Hieischer) to obtain a carbon material dispersion.

[0161] The obtained resin solution and the carbon material dispersion were mixed to obtain a mixed solution 1. Thereafter, using a laboratory ultrasonic homogenizer (UP400S (trade name) manufactured by Dr. Hieischer), the mixed solution 1 was subjected to ultrasonic treatment while being heated at 60°C for 1 hour while being stirred, to obtain a mixed solution 2. The obtained mixed solution 2 was dried under reduced pressure using an evaporator (N-1300 (trade name) manufactured by Tokyo Rikakikai Co., Ltd.), to obtain a dried product.

[0162] The dried product was kneaded for 5 minutes at a processing temperature of 400°C and a rotation speed of 75 rpm using a Labo Plastomill (R-60 (trade name) manufactured by Toyo Seiki Seisakusho) to obtain a resin composition. The composition (mass%) and processing temperature (°C) are shown in Table 3.

[0163] [Examples 15 to 17] (Preparation of resin composition) Resin compositions in Examples 15 to 17 were obtained in the same manner as in Example 14, except that the thermoplastic polymer (A) and the carbon material (B) were changed so as to have the composition shown in Table 3.

[0164] Example 26 (Preparation of resin composition) 24% by mass of thermoplastic polymer (A1), 56% by mass of thermoplastic resin (C3), and 20% by mass of carbon material (B7) were kneaded for 5 minutes at a processing temperature of 360°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (% by mass) and processing temperature (°C) are shown in Table 4.

[0165] [Examples 27 to 31] (Preparation of resin composition) Resin compositions in Examples 27 to 31 were obtained in the same manner as in Example 26, except that the thermoplastic polymer (A) and the thermoplastic resin (C) were changed so as to have the composition shown in Table 4. In Examples 27 to 31, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperature shown in Table 4. The rotation speed and kneading time were the same as in Example 26. The components shown in Table 4 are as described above.

[0166] Example 32 (Preparation of resin composition) 80% by mass of thermoplastic polymer (A1), 20% by mass of carbon material (B7), and 5.0% by mass of inorganic filler (D11) were kneaded for 5 minutes at a processing temperature of 380°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (% by mass) and processing temperature (°C) are shown in Table 4.

[0167] [Examples 33 to 36] (Preparation of resin composition) Resin compositions in Examples 33 to 36 were obtained in the same manner as in Example 32, except that the thermoplastic polymer (A) and the inorganic filler (D) were changed so as to have the composition shown in Table 4. In Examples 33 to 36, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperature shown in Table 4. The rotation speed and kneading time were the same as in Example 32. The inorganic filler (D) shown in Table 4 is as follows.

[0168] (Inorganic filler (D)) (D17) Pana-Tetra...zinc oxide (Panasonic Corporation, Pana-Tetra (registered trademark) WZ-0511 product name), tetrapod-type zinc oxide crystal, aspect ratio: 1) (D18) TISMO D...potassium titanate fiber (TISMO (registered trademark) D (product name) manufactured by Otsuka Chemical Co., Ltd., white needle crystals, aspect ratio: 400) (D19) Twaron...para-aramid fiber (Twaron (registered trademark) manufactured by Teijin Limited, aspect ratio: 250) (D20) T-796H...Glass fiber (T790 DE (product name) manufactured by Nippon Electric Glass Co., Ltd., chopped strand, aspect ratio: 500) (D21) iM16K...glass beads (3M (registered trademark) Glass Bubbles iM16K (product name) manufactured by 3M Co., Ltd., aspect ratio: 1)

[0169] Example 37 (Preparation of resin composition) 80% by mass of the thermoplastic polymer (A1), 20% by mass of the carbon material (B7), and 0.1% by mass of the additive (E1) were kneaded for 5 minutes at a processing temperature of 380°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (% by mass) and processing temperature (°C) are shown in Table 4.

[0170] Example 38 (Preparation of resin composition) A resin composition in Example 38 was obtained in the same manner as in Example 37, except that the thermoplastic polymer (A) and the additive (E) were changed so as to have the composition shown in Table 4. The kneading was carried out at the processing temperature shown in Table 4. The rotation speed and kneading time were the same as in Example 37. The additives (E) shown in Table 4 are as follows.

[0171] (Additive (E)) (E1) CY1770: Antioxidant (CY1770 (product name) manufactured by Solvay Japan Co., Ltd.) (E2) Tinuvin 1600: UV absorber (Tinuvin 1600 (trade name), triazine type, manufactured by BAFS Japan Co., Ltd.)

[0172] Comparative Example 1 (Preparation of resin composition) The thermoplastic resin (C7) was kneaded for 5 minutes at a processing temperature of 200°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (mass%) and processing temperature (°C) are shown in Table 5.

[0173] [Comparative Examples 2 to 18] (Preparation of resin composition) Resin compositions in Comparative Examples 2 to 18 were obtained in the same manner as Comparative Example 1, except that the thermoplastic polymer (A) or the thermoplastic resin (C) was changed so as to have the composition shown in Table 5. In Comparative Examples 2 to 18, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperature shown in Table 5. The rotation speed and kneading time were the same as in Comparative Example 1. The components shown in Table 5 are as described above.

[0174] Comparative Example 19 (Preparation of resin composition) 80% by mass of the thermoplastic polymer (A3) and 20% by mass of the inorganic filler (D3) were kneaded for 5 minutes at a processing temperature of 320°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (% by mass) and processing temperature (°C) are shown in Table 6.

[0175] [Comparative Examples 20 to 95] (Preparation of resin composition) Resin compositions in Comparative Examples 20 to 95 were obtained in the same manner as in Comparative Example 19, except that the thermoplastic polymer (A) or thermoplastic resin (C) and the carbon material (B) or inorganic filler (D) were changed so as to obtain the compositions shown in Tables 6 to 11. In Comparative Examples 20 to 95, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperatures shown in Tables 6 to 11. The rotation speed and kneading time were the same as in Comparative Example 19. The components shown in Tables 6 to 11 are as described above.

[0176] Thereafter, the obtained resin composition was used to obtain 1 / 2 dumbbell test pieces in Examples 2 to 13, 18 to 38, and Comparative Examples 1 to 95 in the same manner as in Example 1. The obtained resin composition was used to obtain U-shaped bearings in Examples 5, 7, 9, 10, 12 to 20, 22, 25, 26, 28, 29, 31, 32, 37, and 38, and Comparative Examples 15, 18, 20 to 29, 34, 35, 38 to 40, and 42 to 58 in the same manner as in Example 1. In the examples and comparative examples, the cylinder temperature and mold temperature in molding the 1 / 2 dumbbell test pieces were changed depending on the resin composition, and the molding was performed at the cylinder temperature and mold temperature shown in each table. In addition, the cylinder temperature and mold temperature in molding the U-shaped bearing were the same as the cylinder temperature and mold temperature in molding the 1 / 2 dumbbell test pieces.

[0177] (Evaluation of Resin Composition) (1) Tensile strength test In the examples and comparative examples, tensile strength tests were carried out using each half dumbbell test piece, and the tensile breaking strength (MPa) was measured in the same manner as in Example 1. The results are shown in Tables 3 to 11.

[0178] (2) Sliding test In the examples and comparative examples, a sliding test was carried out using each U-shaped bearing, and the amount of wear (mg) was calculated in the same manner as in Example 1. The results are shown in Tables 3 to 11.

[0179] Example 39 (Preparation of resin composition) 20% by mass of the thermoplastic polymer (A1) and 80% by mass of the carbon material (B11) were kneaded for 5 minutes at a processing temperature of 380°C and a rotation speed of 75 rpm using a Labo Plastomill device (R-60 (trade name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain a resin composition. The composition (% by mass) and processing temperature (°C) are shown in Table 12.

[0180] The obtained resin composition was press molded using a small test press (Mini Test Press (product name) manufactured by Toyo Seiki Seisakusho Co., Ltd.) at a press temperature of 380°C and a pressure of 5.0 MPa to obtain a test piece (press molded product) having a size of 100 mm square and a thickness of 1 mm. The press temperature (°C) is shown in Table 12.

[0181] [Example 40 and Comparative Examples 96 to 99] (Preparation of resin composition) Resin compositions in Example 40 and Comparative Examples 96 to 99 were obtained in the same manner as in Example 39, except that the thermoplastic polymer (A) or thermoplastic resin (C), and the carbon material (B) or inorganic filler (D) were changed so as to have the composition shown in Table 12. In Example 40 and Comparative Examples 96 to 99, the processing temperature was changed depending on the raw materials, and kneading was performed at the processing temperature shown in Table 12. The rotation speed and kneading time were the same as in Example 39. The components shown in Table 12 are as described above.

[0182] Thereafter, using each of the obtained resin compositions, test pieces (press molded products) in Example 40 and Comparative Examples 96 to 99 were obtained in the same manner as in Example 39. In Example 40 and Comparative Examples 96 to 99, the press temperature was changed depending on the resin composition and was set at the press temperature shown in Table 12. The press pressure was the same as in Example 39.

[0183] (Evaluation of Resin Composition) Electrical resistance test In Examples 39 and 40 and Comparative Examples 96 to 99, the volume resistivity (mΩcm) of each test piece (press molded product) was measured at room temperature (25°C) using a low resistance resistivity meter (Loresta-GXII MCP-T710 (product name) manufactured by Nitto Seiko Analytech Co., Ltd.). The results are shown in Table 12.

[0184] [Table 3]

[0185] [Table 4]

[0186] [Table 5]

[0187] [Table 6]

[0188] [Table 7]

[0189] [Table 8]

[0190] [Table 9]

[0191] [Table 10]

[0192] [Table 11]

[0193] [Table 12]

[0194] [Evaluation of tensile strength test] The tensile breaking strength S of 1 / 2 dumbbell test pieces obtained using the thermoplastic polymer (A) or thermoplastic resin (C) in Comparative Examples 1 to 18 1(MPa, Table 5) and the tensile breaking strength S of 1 / 2 dumbbell test pieces obtained by reinforcing the thermoplastic polymer (A) or thermoplastic resin (C) corresponding to Comparative Examples 1 to 18 with glass fiber (D16), which is a type of inorganic filler (D), in Comparative Examples 71 to 95. 2 Using these values ​​(MPa, Table 11), the strength increase rate (%) was calculated according to the following formula (A). Strength increase rate (%) = tensile breaking strength S 2 / Tensile breaking strength S 1 ×100…(A) As a result, it was found that the maximum strength increase rate was 268% (=150 MPa / 56 MPa×100), calculated from the tensile breaking strengths of Comparative Examples 6 and 81. From this result, in this embodiment, when the strength increase rate of the tensile breaking strength relative to the reference is 269% or more, the strength of the half dumbbell test piece is improved and can be evaluated as passing. Therefore, the tensile breaking strength S 1 The strength increase rate was calculated as a value relative to the strength increase rate. Pass / fail was evaluated based on the strength increase rate. The evaluation results are shown in Tables 13 to 15 and Fig. 6. As shown in Tables 13 to 15 and Fig. 6, it can be seen that the strength of the half dumbbell test piece is improved according to the resin composition of this embodiment.

[0195] [Evaluation of sliding test] A sliding test was carried out in the same manner as in Example 1 using a commercially available sliding material for high speed rotation (NIXAM (registered trademark) 901 (product name), manufactured by Nix Co., Ltd.), and the amount of wear was 24 mg. From these results, in this embodiment, when the wear amount of the U-shaped bearing is 23 mg or less, the wear performance of the U-shaped bearing is improved and can be evaluated as passing. Therefore, pass / fail was evaluated based on the wear amount of each U-shaped bearing in the examples and comparative examples. The evaluation results are shown in Tables 16, 17, and FIG. 7. As shown in Tables 16, 17, and FIG. 7, it can be seen that the wear amount of the U-shaped bearing is improved according to the resin composition of this embodiment. Note that in FIG. 7, the material equivalent to a commercially available sliding material for high-speed rotation is shown as the current material (wear amount: 24 mg).

[0196] [Evaluation of Electrical Resistance Test] One of the applications of this embodiment is a separator for a fuel cell. A prior document (Tsushima Eiki, Carbon Molded Separator Plate for Polymer Electrolyte Fuel Cells, Carbon, No. 218, 2005, pp. 173-177) states that the volume resistivity (electrical resistance value) of a separator plate set by the U.S. Department of Energy is 20 mΩcm or less. Note that the prior document states that the volume resistivity is 20 Ωcm or less, but this is a typo. From this description, it can be considered as one of the indicators of the volume resistivity of a fuel cell separator. In this embodiment, therefore, when the volume resistivity of a test piece (press molded product) is 20 mΩcm or less, the electrical resistance of the test piece is improved and it can be evaluated as passing, so the pass / fail evaluation was performed based on the volume resistivity of the test pieces in the examples and comparative examples. The evaluation results are shown in Table 18. As shown in Table 18, it can be seen that the volume resistivity of the test piece is improved according to the resin composition of this embodiment.

[0197] [Table 13]

[0198] [Table 14]

[0199] [Table 15]

[0200]

Table 16

[0201]

Table 17

[0202]

Table 18

Claims

1. A resin composition comprising a thermoplastic polymer (A) and a carbon material (B), The thermoplastic polymer (A) contains a monomer unit having a dipole moment of 4.1 debye or more, The carbon material (B) has a Raman spectrum obtained by laser Raman spectroscopy at 1360 cm -1 Near and 1580 cm -1 Each peak is shown around 1360 cm -1 The integrated intensity of the peak observed near D And 1580 cm -1 The integrated intensity of the peak observed near G The intensity ratio I D / I G (R value) is 1.80 or less, and 1580 cm -1 The half-width of the peak observed near -1 Below is the Resin composition.

2. The thermoplastic polymer (A) is selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), polyetherimide (PEI), polyamide 66 (PA66), polyethylene terephthalate (PET), liquid crystal polymer (LCP3), liquid crystal polymer (LCP1), polyether ether ketone (PEEK), polyamide 6 (PA6), polyamideimide (PAI), and polyarylate (PAR). The resin composition according to claim 1, which includes at least one selected from the group consisting of polysulfone (PSU), polyphenylsulfone (PPSU), polyamide 10T (PA10T), polyethersulfone (PES), polyetherimide (PEI), polyamide 66 (PA66), polyethylene terephthalate (PET), liquid crystal polymer (LCP3), liquid crystal polymer (LCP1), polyether ether ketone (PEEK), polyamide 6 (PA6), polyamideimide (PAI), and polyarylate (PAR).

3. The resin composition according to claim 1, wherein the carbon material (B) comprises at least one selected from the group consisting of carbon fibers, carbon nanotubes, graphite, and graphene.

4. The resin composition according to claim 1, wherein the aspect ratio of the carbon material (B) is 1.0 or more and 30,000,000 or less.

5. 2. The resin composition according to claim 1, wherein the mass ratio of the thermoplastic polymer (A) to the carbon material (B) (the thermoplastic polymer (A):the carbon material (B)) is 10.0:90.0 or more and 99.9:0.1 or less.

6. The resin composition according to claim 1 , further comprising a thermoplastic resin (C) different from the thermoplastic polymer (A).

7. The resin composition according to claim 6, wherein the content of the thermoplastic resin (C) is 1.0 part by mass or more and 90.0 parts by mass or less per 100 parts by mass of a total of resin solids in the resin composition.

8. The resin composition according to claim 1 , further comprising an inorganic filler (D) different from the carbon material (B).

9. The resin composition according to claim 8, wherein the content of the inorganic filler (D) is 0.1 parts by mass or more and 900.0 parts by mass or less per 100 parts by mass of a total of resin solids in the resin composition.

10. A molded article comprising the resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Conductive resin composition and plastic article using the same

    JP2017171887A